The Effectiveness of Using Scrabble to Increase Students’ Vocabulary Mastery - Nanda hariska; Jusriati; Puspa Sari (Universitas Islam Negeri Palopo, 2025)
This study investigates the effectiveness of using Scrabble as a cooperative learning model to enhance students' vocabulary mastery. The research involved 35 students and employed pre-test and post-test designs to assess the impact of the intervention. Statistical analysis revealed significant improvements in students' vocabulary understanding, with an average pre-test score of 56.3 increasing to 76.0 post-test. The analysis indicated a mean gain of 20 points and a 20% increase in learning outcomes. Normality tests confirmed the data's distribution, and homogeneity tests of variance showed consistent results across the groups. The findings suggest that Scrabble effectively enhances students' vocabulary skills, supported by a t-value of 3.48 (p < 0.05), indicating a significant difference pre- and post-intervention. These results highlight Scrabble's potential as an engaging tool for improving conceptual understanding in educational settings.